Indonesian Junior High School EFL Textbook: Intercultural Pragmatic Perspective - Lisa Sersanawawi; Sholihatul Hamidah Daulay (Institut Agama Islam Negeri (IAIN) Manado, 2023)
This research was conducted to describe the intercultural pragmatic perspective in the grade 8 Indonesian Junior High School EFL textbook entitled “When English Rings a Bell”. Researchers hope that the result of this study can increase teachers’ awareness’ of interculturality in Indonesia, so that they are able to provide language material that can be linked to the learning process. In this study, researcher used content analysis. The text can be in visual form which is used as a communication tool such as documents, film, picture, and book. In this study, researcher used a book entitled “When Rings a Bell” 8th grade Junior high school. In general, this book has been previously used by Junior high school students in Indonesia which was designed by the Ministry of Education and Culture of the Republic of Indonesia in 2014 but revised again in 2018. Researcher used Moran’s (2001) theory as a data analysis on cultural aspect in English textbook.Keywords: intercultural perspective, EFL textbook, junior high school